Pertukaran massa air di Laut Jawa terhadap periodisitas monsun dan Arlindo pada tahun 2015 - Selvita Nurani Siregar; Lintang P. Sari; Noir P. Purba; Widodo S. Pranowo; Mega L. Syamsuddin (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2017)
The Java Sea with a surface area about 467.000 km2, is located in the South East Sunda Shelf with the average of depth is 40 meters, affected by several phenomena, whether physical or meteorological. This research aims to analyze the characteristics of water masses in the Java Sea and its relationship with the periodicity of the monsoon and Indonesian Throughflow Water (ITF) phenomenon. Then analyze the exchange of water masses in the Java Sea. The data used are temperature and salinity to identify the characteristics of the water masses. Ocean currents data to identify ITF patterns and winds data to identify the monsoon patterns. The data used in 2015 from the Infrastructure Development of Space Oceanography (INDESO) sites with a resolution of 1/12°. The method used is a descriptive analysis of spatially and temporally. The results show that averaging seasonal found that southeast monsoon period salinity is higher (31-34 psu) than northwest monsoon period (29.5-33 psu), and southeast monsoon period temperature is lower (27-30.5°C) than northwest monsoon period (28.5-30.5°C). ITF phenomenon occurs in May through September and reaches its peak in June, July, and August. ITF strengthened in southeast monsoon and weakened in the northwest monsoon. ITF and monsoon have similar impacts on salinity and temperature in the Java Sea. The water masses in the Java Sea comes from the South China Sea and Makassar Strait. In the northwest monsoon, Java Sea filled by water masses of the South China Sea, while in the southeast monsoon phenomenon which coincides with ITF phenomenon, Java Sea water masses is filled by water masses from Makassar Strait. In the transition monsoon I and II, the Java Sea filled by the South China Sea and the Makassar Strait water masses. Laut Jawa dengan luas permukaan sekitar 467.000 km2, terletak dibagian tenggara paparan Sunda dengan kedalaman rata-rata adalah 40 meter dipengaruhi oleh beberapa fenomena, baik fisikal maupun meteorologikal. Penelitian ini bertujuan untuk mendapatkan informasi mengenai karakteristik massa air di Laut Jawa dan hubungannya dengan periodisitas monsun serta fenomena arlindo dan menganalisis pertukaran massa air di Laut Jawa. Data yang digunakan adalah suhu dan salinitas untuk mengidentifikasi karakteristik massa air. Arus untuk mengidentifikasi pola arlindo dan angin untuk mengidentifikasi pola monsun. Data yang digunakan tahun 2012 dari situs infrastructure development of space oceanography (INDESO) dengan resolusi 1/12°. Metode yang digunakan adalah deskriptif dengan pendekatan analisis secara spasial dan temporal. Berdasarkan hasil perata-rataan musiman didapatkan bahwa salinitas saat monsun timur lebih tinggi (31-34 psu) daripada saat monsun barat (29,5-33 psu), dan suhu saat monsun timur lebih rendah (27-30,5°C) daripada saat monsun barat (28,5-30,5°C). Fenomena arlindo terjadi pada bulan Mei sampai September dan mencapai puncaknya pada bulan Juni, Juli, dan Agustus. Arlindo menguat pada monsun timur dan melemah pada monsun barat. Monsun dan arlindo memiliki pengaruh yang sama terhadap salinitas dan suhu di Laut Jawa. Massa air di Laut Jawa berasal dari Laut Cina Selatan dan Selat Makassar. Pada monsun barat, Laut Jawa diisi oleh massa air Laut Cina Selatan, sedangkan pada monsun timur yang bertepatan dengan fenomena arlindo, massa air Laut Jawa diisi oleh massa air Selat Makassar. Pada monsun peralihan I dan II, Laut Jawa diisi oleh massa air Laut Cina Selatan dan juga Selat Makassar.